The analysis of inter- and intrapopulation variability of Milnesium eurystomum Maucci, 1991 reveals high genetic divergence and a novel type of ontogenetic variation in the order Apochela. Issue 6 (17th August 2020) - Morek, Witold; Blagden, Brian; Kristensen, Reinhardt M.; Michalczyk, Łukasz
Abstract : Tardigrada are a phylum of cosmopolitan invertebrates inhabiting both terrestrial and marine ecosystems. The carnivorous species are usually characterized by a wide buccal tube, which constitutes the first and rigid part of the digestive system. Among tardigrades, only the genus Milnesium is considered exclusively carnivorous and includes the largest known species in the phylum. Some members of the genus exhibit developmental variability in taxonomically important morphological traits such as the number of points on the secondary branches of claws and cuticular sculpturing. Milnesium eurystomum is one of the largest tardigrades, with body length reaching 1.2 mm, and it is equipped with an exceptionally wide buccal tube, enabling this animal to feed on various prey, including other tardigrade species. Importantly, M. eurystomum, as well as other species with wide buccal tubes, were described solely using mature females, thus their developmental variability remains unknown. Interestingly, small Milnesium specimens with remarkably wide buccal tubes have never been reported, raising a question of whether such hatchlings and juveniles (first and second life stages) are extremely rare and simply have never been reported, or their buccal apparatus morphology is different from adults and thus constitutes as an undescribed buccal tube developmental variability. To answer this question, we analysed four populations of M. eurystomum originating from Greenland, Svalbard and Scotland. Due to discrepancies in species delineation based on different types of data, we parallelly applied various methods of species delimitation, both morphological and molecular. Thanks to ontogenetic analysis, we show and describe a novel type of developmental variability in the size and shape of the buccal tube. We also provide novel morphological traits and data for this species, together with the first record and characterization of males. Finally, we discuss the consequences of our findings for the taxonomy of Milnesium and tardigrades in general.